Diseño De Una Planta De Tratamiento De Aguas Residuales Para Su Reutilización En Riego En Áreas Verdes - Mena, Mayra Elizabeth Cáceres; Guadalupe, Carla Sofía Arguello; Vallejo, Marco Vinicio Pino; Córdova, Galo Briam Montenegro; Bernal, Catalina Margarita Verdugo; Suárez, Jaime Giovanny Béjar; Mena, Andrés Paúl Cáceres (European Scientific Journal, ESJ, 2017)
Over the last few years uncontrolled wastewater discharges have been generated in bodies of water which pose a high risk to the environment and human health. The present study is based on a laboratory prototype under controlled conditions with the aim: To return water quality indexes to safe conditions within the “Edison Riera” Campus at National University of Chimborazo for its reuse in the green areas irrigation, through unit processes based on the percentages reduction results of polluting organic matter and applying treatment processes by activated sludge. During the investigation the following results were obtained: Efficiency and reduction of biological and chemical oxygen demand by 93.75%, and 85.02%, coliforms color and turbidity decrease in 87.51%, 93.84% and 90.29% simultaneously, the same ones that have allowed designing a waste water treatment plant for irrigations in green areas in real scale.